Participatory rural energy planning - "Malhotra, Preeti" (New Delhi, 1998)
This Handbook on Participatory Rural Energy Planning is a direct response to the ever-growing need to conceptualize decentralized planning and implementation of rural energy interventions with the active involvement of local communities, especially women; and provide methodological tools to facilitate the process. The methodology, presented in this Handbook as a step-by-step procedure, has been evolved by TERI researchers, from a two-year action research project conducted in a few villages in the Gurgaon district of the north -western state of Haryana.
Keywords: Rural energy